2016
DOI: 10.4088/pcc.15m01824
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Continuous Identity Disturbances, Negative Mood, and Suicidal Ideation

Abstract: Lack of continuous identity predicted both depression and suicidality severity. Integration of perceived identities may be a worthwhile goal for behavioral interventions aimed at reducing depressed mood and suicidality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…Second, the present research measured participants' self-continuity in a broader range of time scopes: across past, present, and future selves. Little research has examined selfcontinuity from the past and to the future simultaneously, with some notable exceptions (e.g., Sokol & Eisenheim, 2016). Consistent with Sokol and Eisenheim (2016), we found that past self-continuity and future self-continuity are positively associated, with correlation coefficients ranging between .48 and .56.…”
Section: Discussionsupporting
confidence: 85%
“…Second, the present research measured participants' self-continuity in a broader range of time scopes: across past, present, and future selves. Little research has examined selfcontinuity from the past and to the future simultaneously, with some notable exceptions (e.g., Sokol & Eisenheim, 2016). Consistent with Sokol and Eisenheim (2016), we found that past self-continuity and future self-continuity are positively associated, with correlation coefficients ranging between .48 and .56.…”
Section: Discussionsupporting
confidence: 85%
“…35 Individuals in a state of anxiety tend to think more negatively and may feel more negatively towards the meaning of life, and are prone to suicide. 36 In addition, anxiety may cause changes to physiological indexes, such as sleep, which may also cause suicidal ideation. 37 Inflammatory conditions, such as increased CRP levels may also affect suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…These processes include autobiographical memory, a narrative construction that develops to integrate diverse experiences to allow a persisting self-representation, the awareness of a body that is perceived as belonging to oneself, and a representation of one’s qualities, values, and characteristic ways of engaging with oneself and others (i.e., personality; e.g., Lampinen et al, 2004 ). The bringing together of disparate elements over time into a sense of oneself persisting from past to present (and future) has been variously referred to as diachronic unity, diachronicity, continuous identity or a temporally extended self ( Braude, 1995 ; Radden, 1996 , 1999 ; Lampinen et al, 2004 ; Klein, 2012 ; Prebble et al, 2013 ; Sokol and Eisenheim, 2016 ). In adulthood, many people will appraise that despite major psychological and bodily changes, they remain the same person they were earlier in their life.…”
Section: Introductionmentioning
confidence: 99%